Investigation of Instructional and Distributed Leadership Behaviors of School Administrators - Özat, Şemsi Kardelen; Cemaloğlu, Necati (Technium Social Sciences Journal, 2026)
The purpose of this study is to examine the instructional and distributed leadership behaviors of school administrators based on teacher perceptions and to determine whether these behaviors differ according to selected variables. The study population consists of teachers working in public primary schools in Ankara during the 2024-2025 academic year, with a sample of 375 teachers selected via random sampling. Data were collected using the Personal Information Form, the Instructional Leadership Scale, and the Distributed Leadership Inventory. Descriptive statistics, t-tests, and ANOVA were employed for data analysis. The findings indicate that school administrators exhibit distributed leadership behaviors at a "very high" level and instructional leadership behaviors at a "high" level. While female teachers rated distributed leadership functions significantly higher than male teachers, no significant difference was found based on gender regarding instructional leadership behaviors. Furthermore, no statistically significant differences were observed in either leadership style regarding teachers' length of service or marital status. Consequently, it is concluded that while administrators are effective in executing leadership functions, "leadership team cohesion" scores were relatively lower, suggesting a need for improvement in collaborative dynamics.